Induction of DNA double-strand breaks and cellular senescence by human respiratory syncytial virus. Issue 4 (18th May 2016) - Martínez, Isidoro; García-Carpizo, Verónica; Guijarro, Trinidad; García-Gomez, Ana; Navarro, Diego; Aranda, Ana; Zambrano, Alberto
ABSTRACT: Human respiratory syncytial virus (HRSV) accounts for the majority of lower respiratory tract infections during infancy and childhood and is associated with significant morbidity and mortality. HRSV provokes a proliferation arrest and characteristic syncytia in cellular systems such as immortalized epithelial cells. We show here that HRSV induces the expression of DNA damage markers and proliferation arrest such as P-TP53, P-ATM, CDKN1A and γH2AFX in cultured cells secondary to the production of mitochondrial reactive oxygen species (ROS). The DNA damage foci contained γH2AFX and TP53BP1, indicative of double-strand breaks (DSBs) and could be reversed by antioxidant treatments such as N-Acetylcysteine (NAC) or reduced glutathione ethyl ester (GSHee). The damage observed is associated with the accumulation of senescent cells, displaying a canonical senescent phenotype in both mononuclear cells and syncytia . In addition, we show signs of DNA damage and aging such as γH2AFX and CDKN2A expression in the respiratory epithelia of infected mice long after viral clearance. Altogether, these results show that HRSV triggers a DNA damage-mediated cellular senescence program probably mediated by oxidative stress. The results also suggest that this program might contribute to the physiopathology of the infection, tissue remodeling and aging, and might be associated to long-term consequences of HRSV infections.